TOOLS FOR PERSONALIZED LEARNING-BASED TEACHER EDUCATION - Rutkiene, Ausra; Kaminskiene, Lina; Alisauskiene, Stefanija; Milteniene, Lina; Kazlauskiene, Ausra; Siriakoviene, Asta; Guðjónsdóttir, Hafdis; Kristinsdóttir, Jónína Vala; Wozniczka, Anna Katarzyna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Changes in the education from a teacher-centered to a student-centered approach requires changes in schools and in teacher education. One of possible ways is personalized learning (PL). It is a new concept in many countries around the world. PL is closely related to individualized, differentiated learning, inclusive education principles (Abbot, 2014; EDUCAUSE, 2013). PL builds on an understanding of learner: individual development, seeking of personal goals, taking into consideration individual differences and inclusion. PL “challenges teachers to search for pedagogy and practices that will help them addressing diversity in their classroom” (Guðjónsdóttir, 2000, p.9). Different methods and tools (e-tools as well) might be used for PL such as digital storytelling, three step interview, e-portfolio. Paper presents theoretical analysis of links between aspects of effective learning (good knowledge of each student; shared teacher and student responsibility within the learning process; personal learner involvement, linking to individual motivation, experience, and aspirations; collaboration, participation and involvement in the learning process; effective use of information technology and other learning resources (Williams, 2013)) and methods/tools for PL.